Multiplex reverse transcription-PCR for surveillance of influenza A and B viruses in England and Wales in 1995 and 1996. - Ellis, J S (1997)
Multiple-target (multiplex) reverse transcription-PCR (RT-PCR) for detection, typing, and subtyping of the hemagglutinin gene of influenza type A (H3N2 and H1N1) and type B viruses was developed and applied prospectively to virological surveillance of influenza in England in the 1995-1996 winter season. During this season both influenza A H3N2 and H1N1 viruses were circulating, although at different times. Six hundred nineteen combined nose and throat swabs taken by general practitioners in sentinel practices from individuals presenting with "influenzalike illness" were analyzed by culture, multiplex RT-PCR, and immunofluorescence. Of the 619 samples, 246 (39.7%) were positive by multiplex RT-PCR compared with 200 (32.3%) which yielded influenza viruses on culture. There was 100% correlation between multiplex RT-PCR typing and subtyping and the influenza types and subtypes obtained from culture. There was also excellent correlation between the temporal detection of influenza A H3N2 and H1N1 viruses by multiplex RT-PCR and by culture. During the peak weeks of influenza virus activity, a total of 259 specimens were received, of which 101 (38.9%) yielded influenza viruses on culture while 149 (57.5%) were positive in multiplex RT-PCR, providing an increase in detection of influenza viruses of approximately 20%. The increased detection of influenza virus occurred in all the age groups sampled. Samples which were positive by multiplex RT-PCR but negative by culture were not detected significantly earlier or later in the winter of 1995-1996 but were detected during the peak weeks of clinical influenza virus activity. Multiplex RT-PCR was successfully used in surveillance of influenza to provide accurate, sensitive diagnosis directly on clinical specimens sent through the post.